2021
DOI: 10.3389/fsurg.2021.685868
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Peritoneal Fluid Examination for Free Cancer Cells in Patients Qualified for Surgery for Gastric Cancer

Abstract: Background: Peritoneal lavage cytology in patients with gastric cancer may correlate with an unfavorable prognosis. This study evaluated the presence of free cancer cells in the peritoneal lavage of a population of patients with gastric cancer and its correlation with the outcome of surgical treatment.Methods: One hundred patients diagnosed with gastric or gastrointestinal junction adenocarcinoma underwent surgery. In all patients, a cytological and immunohistochemical analysis of peritoneal lavage was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
3
0
2
Order By: Relevance
“…Gastric cancer patients with positive cytology typically have poor prognoses[ 15 ]. Individuals with positive cytology generally exhibit superior survival rates to those with visible peritoneal metastases[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer patients with positive cytology typically have poor prognoses[ 15 ]. Individuals with positive cytology generally exhibit superior survival rates to those with visible peritoneal metastases[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thống kê thấy rằng tỷ lệ bắt gặp tế bào ung thư tự do ở dịch rửa KPM trong phẫu thuật UTDD dao động từ 4 -41% và phụ thuộc vào các phương pháp lựa chọn kiểm tra: tế bào học truyền thống, hoá mô miễn dịch (HMMD) hay phản ứng khuếch đại chuỗi (PCR). [1], [2], [3], [4], [5], [6], [7], [8] Hiện nay, mặc dù trên thế giới, nghiên cứu về lĩnh vực này đã hạn chế phần nào tính thời sự; tuy nhiên, tại Việt Nam đây vẫn là chủ đề cần được khai thác tìm hiểu chuyên sâu; trong khi ở Bệnh viện K -một trung tâm ngoại khoa ung thư tiêu hoá hàng đầu của cả nước với số lượng BN phẫu thuật UTDD hàng năm rất lớn; vì vậy xuất phát từ các yêu cầu thực tiễn, nhóm nghiên cứu chúng tôi tiến hành thực hiện đề tài: "Đánh giá kết quả phân tích tế bào học dịch rửa khoang phúc mạc trong phẫu thuật ung thư dạ dày" với mục tiêu:…”
Section: đặT Vấn đềunclassified
“…Tuy nhiên mặc dù đặc điểm khối u có thành phần chế nhầy hay tế bào nhẫn đều là loại mô bệnh học có độ ác tính cao; xu hướng xâm nhập tạng lân cận và cấy ghép phúc mạc nhưng thực tế 02 trường hợp chẩn đoán tế bào học dịch rửa KPM (+) của chúng tôi đều không ghi nhận sự hiện hiện của loại mô học này có thể do hạn chế về cỡ mẫu nghiên cứu. [1], [2], [3], [4], [5], [6], [7], [8] V. KẾT LUẬN Qua nghiên cứu về phương pháp rửa KPM ở 39 trường hợp UTDD được phẫu thuật triệt căn tại khoa Ngoại Bụng I -Bệnh viện K, chúng tôi thu được kết quả phân tích tế bào học dịch rửa KPM dương tính là 5% và kỹ thuật áp nhuộm tế bào thường quy cũng như kỹ thuật khối tế bào (cell -block) được thực hiện phổ biến (97,4%). Chúng tôi chưa ghi nhận yếu tố mô bệnh học có mối liên quan với tình trạng dịch rửa KPM trong phẫu thuật UTDD (p>0,05).…”
Section: đặT Vấn đềunclassified
“…PC can further improve the efficacy of SL for GC staging through the identification of occult carcinomatosis [ 54 ]. Indeed, positive PC is associated with an independent prognostic factor for poor prognosis and recurrence following curative gastric resection [ 55 , 56 , 57 , 58 ]. A systematic review of the accuracy of peritoneal washing in GC patients revealed a disease recurrence rate of 11.1–100% and 0–51% in the case of positive and negative PC, respectively [ 59 ].…”
Section: Performance and Clinical Significance Of Sl With Pcmentioning
confidence: 99%